Space debris material sourcing for in-space manufacturing: a quantitative evaluation framework - Lenkart, Madeline; Biller, Stephan (Frontiers in Space Technologies, 2026)
The increasing accumulation of space debris presents significant challenges to sustainable space exploration while offering opportunities for material reuse through in-space manufacturing. This research presents a framework for deriving the comprehensive value associated with using the growing space debris population as a material sourcing option for future in-space manufacturing. The growth rate of the space debris population in low Earth orbit is derived using a material flow analysis for future launch rate estimates up to the year 2050. Using these estimates, a total value calculation for space debris material sourcing is determined by considering the value associated with space debris’s material market value, transportation cost reduction, and object removal risk reduction. The results of this framework indicate that cost savings from reduced material transportation to space are the most significant driver for overall space debris value, significantly outweighing the contributions of material and risk reduction value. As more data become available regarding in-space manufacturing capabilities, this framework provides insights regarding the composition of space debris value and assesses the economic viability of space debris reuse.